Competition and Debt Conservatism - Armitage, Seth; Leung, Woon Sau (Journal of Financial and Quantitative Analysis, 2026)
Abstract Exploiting changes in countries’ competition laws, we find that competition increases firms’ propensity to use zero leverage (ZL). We test the financial-flexibility, financial-constraint, and quiet-life explanations for this result, concluding that desire for flexibility is the one most likely. The relation between competition and ZL strengthens with cash-flow volatility, which supports the flexibility motive. Adoption of ZL by firms is accompanied by increases in payouts, so it is unlikely that ZL adopters are constrained. Proxies for governance have no effect on the relation between competition and ZL, suggesting that desire for a quiet life is not the explanation either.